PP293 Tiered Rapid Response Products In The Evidence Directorate Of Healthcare Improvement Scotland. (December 2021) - Anand, Neil; Campbell, Evan; Macgann, Tracey; Macpherson, Karen; Muniz, Tomas
Abstract : Introduction: The Evidence Directorate produced eighteen rapid responses during the early stages of the COVID-19 pandemic. To address this need while retaining methodological integrity a three-tiered system for rapid responses was developed. Methods: All rapid responses answer specific research questions rather than broad health system issues. The appropriate level varies depending on the time and resource available, and the requester's need: Level 1 – Reference List (turnaround 4–8hrs, delivered by an information scientist): a quick search for best available evidence, and results presented as a reference list. Level 2 – Summary of evidence (turnaround 1–2 days, delivered by an information scientist): a quick search and brief summary of the best available evidence. Level 3 – Synthesis of evidence (turnaround 3–7 days, delivered by a Health Services Researcher or Health Economist): a quick search and then a narrative summary and synthesis of the best available evidence, with a brief appraisal of validity, reliability and generalizability. Results: Since the launch of the three-tiered model in September 2020 there have been five rapid responses. Two were Level 2 products and three were Level 3 products. Conclusions: The Evidence Directorate of Healthcare Improvement Scotland now has an agile rapid response product which can be applied to a variety of settings and needs. This was borne out of a need for a rapid turnaround and evidence synthesis during the COVID-19 pandemic.